UI/UX Design of Early Childhood Learning Applications Using Figma: Perancangan UI/UX Aplikasi Pembelajaran Anak Usia Dini Menggunakan Figma - Ranti Eka Putri; Yanti Yusman; Yuda Wira Pratama (Universitas Singaperbangsa Karawang, 2022)
In Presidential Regulation (Perpres) Number 60 of 2013, early childhood is a newborn to children who are not even 6 years old. From an educational point of view, this early age is a golden period in the development of a child's brain so that the Little One must be given the right stimulus or stimulus. Usually most children, especially children in the age range of 4 to 6 years, get knowledge from their parents or attend kindergarten. The background of this research is because there are still very few learning media that can be used for early childhood learning. The purpose of this study is to design a ui/ux application for early childhood where the method used is the prototype method using figma, and it contains material that will be learned by early childhood such as material on hijaiyah letters, hadith, prayer readings, selected letters, daily prayers, numbers, alphabets and themes. In the theme there are five materials that will be included, namely professions, colors, fruits, animals and transportation. This prototype is a reference for building early childhood learning applications.